Formulation, Optimization, and Ex-vivo Evaluation of Novel Lipid Carriers for Enhanced Transdermal Delivery of Hydroquinone - Verma, Shivani; Kaur, Sukhjinder; Kumar, Lalit (Micro and Nanosystems, 2021)
Background: HQ is used for hyper-pigmentation treatment using conventional creams and gels. These formulations show various disadvantages like poor skin permeation, allergic reactions, and repeated use and decreasing patient compliance. Objectives: The present work involved formulation, statistical optimization, and characterization of Nanostructured Lipid Carriers (NLCs) for efficient topical delivery of hydroquinone (HQ) for hyperpigmentation treatment. Methods: The NLCs were optimized exploring Box–Behnken Design (BBD) using three independent variables and two dependent variables. Formulation having the minimum size and maximum drug entrapment was considered as optimized formulation. The optimized formulation was evaluated for drug release followed by its freeze-drying. The freeze-dried formulation was subjected to Differential Scanning Calorimetry (DSC) analysis, X-Ray Diffraction (XRD) analysis, and Fourier Transform-Infrared spectroscopy (FT-IR) analysis. Furthermore, NLCs based gel was prepared by using Carbopol 934 as a gelling agent. NLCs based gel was evaluated for skin permeation, skin retention, and skin distribution (through confocal microscopic analysis) using pig ear skin. Results: Optimized NLCs showed smaller particle size [(271.9 ± 9) nm], high drug entrapment [(66.4 ± 1.2) %], tolerable polydispersity index (PDI) (0.221 ± 0.012), and zeta potential [(-25.9 ± 1.2) mV]. The FT-IR analysis revealed excellent compatibility between HQ and other excipients. The Carbopol 934 gel containing NLCs showed high transdermal flux [(163 ± 16.2) μg/cm2/h], permeability coefficient (0.0326 ± 0.0016), and skin permeation enhancement ratio (3.7 ± 0.4) compared to marketed cream of HQ. The results of confocal microscopic (CLSM) analysis revealed the accumulation of optimized NLCs in the lower epidermal layers of skin. Conclusion: NLCs based gel was considered effective in the topical delivery of HQ to treat hyperpigmentation due to high skin permeation, skin retention, and prolonged release of HQ.
Keywords: Transdermal flux